2020
DOI: 10.1016/j.amjsurg.2019.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive sigmoidectomy for diverticular disease decreases inpatient opioid use: Results of a propensity score-matched study

Abstract: a b s t r a c tBackground: Patients undergoing gastrointestinal surgery are at high risk for postoperative opioid use. Methods: We evaluated inpatient opioid use among patients undergoing sigmoidectomy for diverticular disease from the Premier Hospital Database and compared across surgical approaches using propensity score-matching analysis. Results: After the day of surgery, minimally invasive (MIS) patients were administered significantly lower doses of parenteral opioids (median daily morphine milligram equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, RS patients had shorter mean index hospital LOS, lower conversion-to-open surgery rates and less mean hospital outpatient visits after surgery when compared to the LS group. These findings likely reflect longterm MIS colectomy benefits that include faster recovery with fewer complications and less pain [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, RS patients had shorter mean index hospital LOS, lower conversion-to-open surgery rates and less mean hospital outpatient visits after surgery when compared to the LS group. These findings likely reflect longterm MIS colectomy benefits that include faster recovery with fewer complications and less pain [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 91%
“…The development and introduction of minimally invasive surgery (MIS) tools and approaches have fundamentally changed colorectal surgery. MIS approaches to colorectal surgery offer several outcomes advantages over traditional open surgery (OS) that include earlier return of bowel function, less postoperative pain and opioid use, shorter hospital length of stay (LOS), and fewer surgical site infections [1][2][3][4][5]. The adoption of the MIS approach to colorectal surgery increased from 40 to 60% in 2011 to 75% in 2018 [6].…”
mentioning
confidence: 99%
“…Previous studies reported that robotic-assisted surgery is associated with reduced postoperative pain [ 5 , 6 ]. However, there is limited literature examining the potential benefit of the robotic approach in reducing short-term and long-term opioid use [ 7 , 8 ], particularly for colectomies.…”
mentioning
confidence: 99%
“…In an analysis of thoracic lobectomy procedures from the Premier database, robotic patients received opioids less frequently, and with lower total and average daily doses, compared to those undergoing VATS and open procedures [ 24 ]. In a similar analysis of sigmoidectomies, robotic patients were administered lower doses of parenteral opioids in comparison to open or laparoscopic patients [ 25 ]. These findings are consistent with the results of an analysis within our own institution, where we found that minimally invasive techniques were associated with a reduced risk of prolonged opioid use [ 26 ].…”
Section: Discussionmentioning
confidence: 99%